2022
DOI: 10.30541/v43i1pp.27-51
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Primary Education in Rural Pakistan

Abstract: Highly subsidised public schools are the principal provider of education in the rural areas of Pakistan. Steady growth of school age population over time coupled with stagnant public funding has put enormous pressure on this system. The alternative of cost recovery through user charges has its own critics. They argue that introduction of tuition fees would substantially reduce the already small representation of low-income households in primary schools due to high pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
2
6
0
2
Order By: Relevance
“…Our results are somewhat similar to findings in Hamid and Siddiqui (2001) in which demand for schooling by gender is studied for three major cities of Pakistan i.e., Faisalabad, Sialkot and Karachi and it is found that increase in father's education raises the schooling of both sons and daughters but mother's education has significant impact only on daughters' schooling. Similarly the role of parental education in defining the schooling outcomes of children, as is evident from findings of the study in hand, is also supported by empirical evidence presented in Saqib (2004), whereby it is found that there is much higher likelihood of a male child attending primary school compared to a female child and that this likelihood of enrolment increases for children with educated fathers in rural Pakistan.…”
Section: Resultssupporting
confidence: 66%
“…Our results are somewhat similar to findings in Hamid and Siddiqui (2001) in which demand for schooling by gender is studied for three major cities of Pakistan i.e., Faisalabad, Sialkot and Karachi and it is found that increase in father's education raises the schooling of both sons and daughters but mother's education has significant impact only on daughters' schooling. Similarly the role of parental education in defining the schooling outcomes of children, as is evident from findings of the study in hand, is also supported by empirical evidence presented in Saqib (2004), whereby it is found that there is much higher likelihood of a male child attending primary school compared to a female child and that this likelihood of enrolment increases for children with educated fathers in rural Pakistan.…”
Section: Resultssupporting
confidence: 66%
“…The results of this study are also reinforced by research conducted by (Saqib, 2004) on the willingness to pay (WTP) in primary schools in rural Pakistan. The study shows that access to travel time to school has an effect on willingness to pay parents in rural areas of Pakistan.…”
Section: Resultssupporting
confidence: 63%
“…A number of studies have been conducted to analyse the determinants of primary school enrolment in Pakistan. A detailed review of the studies on this subject by Chishti and Lodhi (1988), Sathar and Lloyd (1994), Burney andIrfan (1991, 1995), and Alderman, et al ( , 2001) can be found in Saqib (2004). These studies are based on a variety of databases with diverse coverage.…”
Section: Review Of Literaturementioning
confidence: 99%